Prediction of speed of sound and specific heat capacity of ionic liquids using predictive SAFT-based equation of state. (16th January 2023) - Majdi, Hasan Sh.; Faisal Raheem, Al-Behadili; Jasim Abdullah, Siham; Mourad Mohammed, Ibrahim; Yasin, Yaser; Yadav, Anupam; Hadrawi, Salema K.; Shariyati, Reza
Graphical abstract: Research highlight: The predictive PC-SAFT EoS has been utilized to predict the speed of sound, the isochoric and isobaric heat capacity of ionic liquids. The surface area and molecular volume of the UNIFAC model have been used to estimate the segment number and hard sphere diameter. The predictive PC-SAFT model can predict the specific isochoric and isobaric heat capacity of ILs up to high pressure, accurately. Abstract: In this work, the predictive PC-SAFT EoS has been developed to predict the speed of sound, the isochoric and isobaric heat capacity of ionic liquids (ILs) over a wide range of pressures and temperatures. In this new methodology, the segment number and diameter of ILs have been estimated using the surface area and molecular volume of the UNIFAC model. The segment energy and association energy parameters have been obtained using an inverse relationship between dispersion/association energy and segment diameter. The results show that the predictive PC-SAFT model can predict the specific isochoric and isobaric heat capacity of ILs up to high pressure, accurately. In the case of the speed of sound, the model performance is acceptable by considering using no adjustable model parameters. To check the model capability, the new model results have been compared to the electrolyte PC-SAFT EoS.